Effect of Early Post-hatch Feeding on Nutrient Digestibility, Carcass Characteristics, Gut Morphology and Livability of Commercial Broiler Chicken - Desai, Dharmikkumar M.; Vahora, S. G.; Rajpura, R. M.; Patel, M. M.; Panchal, D. P.; Raut, L. B. (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted from February to March 2024 at the Poultry Research Station, VASREU, Kamdhenu University, Anand, India to study the effect of early post-hatch feeding on commercial broiler chicken performance. A total of 144 days-old broiler chicks were assigned to four groups based on body weight, with 36 chicks in each group. The control group received water and pre-starter feed immediately upon arrival, while T1, T2, and T3 groups received feed and water 12, 24, and 0 hours post-arrival, respectively. A metabolic trial was conducted at 6 weeks of age. Gut morphology was assessed on days 7, 21, and 42, and carcass characteristics were evaluated on day 42. Nitrogen balance was significantly higher in the OF, D12, and C groups than in D24 (p<0.05), with early feeding improving nitrogen retention. Nutrient retention of calcium, phosphorus, dry matter, crude fat, and crude fiber showed no significant differences across treatments. Dressing percentage was similar for all treatments, but abdominal fat was highest in D24 and lowest in C, with intermediate levels in D12 and OF. Delayed feeding reduced villi height, width, and crypt depth in the duodenum but did not affect the villi-to-crypt depth ratio. In the jejunum, delayed feeding decreased villi width and crypt depth, but increased the villi-to-crypt depth ratio. Liveability remained unaffected by the feeding and watering schedule.